Design, synthesis, and biological activity of N-alkylated analogue of NCL1, a selective inhibitor of lysine-specific demethylase 1. Issue 3 (6th October 2014) - Ahmed Khan, Mohammed Naseer; Tsumoto, Hiroki; Itoh, Yukihiro; Ota, Yosuke; Suzuki, Miki; Ogasawara, Daisuke; Nakagawa, Hidehiko; Mizukami, Tamio; Miyata, Naoki; Suzuki, Takayoshi
Abstract : A hybridization of NCL1 and compound5 led to the identification of a potent lysine-specific demethylase 1 inhibitor5 . Abstract : Lysine-specific demethylase 1 (LSD1), the first histone demethylase to be identified, catalyzes specifically the demethylation of the mono- and dimethyl groups of histone H3 lysine 4, and its dysregulation is thought to contribute to the development of cancer. We have recently reported that NCL1 (4 ) is the first cell-active LSD1-selective inhibitor. To find LSD1 inhibitors that show higher potency than NCL1 (4 ), we designed and synthesized an N -alkylated analogue of NCL1 (5 ), and evaluated its biological activity. In enzyme assays, compound5 was six times more potent than4, and compound5 exhibited cell growth inhibition in cervical cancer HeLa cell line and neuroblastoma SH-SY5Y cell line. Compound5 should be useful as a lead structure for anticancer drugs.